COMPARATIVE STUDY OF AGRICULTURAL LIGNOCELLULOSIC BIOMASS DELIGNIFICATION BY MICROWAVE ASSISTED CHEMICAL PRETREATMENT - MUHAMMAD LAGHARI, SHUAIB (2016)
Environmental concerns caused by fossil fuels coupled with growing energy demands have pushed nations to seek other forms of energy/renewable energy. Biofuels production from plant waste seems to be a good option, due to its usabilityin transportation sector, renewable nature andworldwide availability. Huge quantities of lignocellulosic agricultural wastes are generated in the form of rice husk, palm fiber empty fruit bunch, and coconut husk. They have good potential to be used as alternate energy. Their extraordinary lignin portion, has, posedstrainontheir use. Thisworkexplored thepossibility of usingmicrowave frequency based energies combined with alkaline and acidic treatments for delignification of these agricultural biomass waste to enhance their energy potential.